SYNTHESIS OF TERPOLYMER OF ETHYL ACRYLATE (EA), N-BUTYL ACRYLATE (N-BA) ANDBUTYL METHACRYLATE (BMA) ANDSOLUTION BLENDING WITH CHLORINATED RUBBER (CR) (Biological Sciences - PJSIR, 2001)
Free radical terpolymerization of ethylacrylate, n-butyl acrylate and butyl methacrylate has been carried out at 95°C using benzoyl peroxide as initiator. It has been observed that the three monomers polymerized simultaneously and form terpolymer in all monomeric ratios. EA enters in the growing polymer chain more rapidly than n-BA and BMA. The terpolymers of 24130-38575 molecular weight are obtained. All terpolymer samples are highly tacky transparent viscous material. The refractive index of terpolymer samples ranges 1.495-1.497. It may be used as tackifying agent in the preparation of adhesive. Besides, the blends of chlorinated rubber and terpolymer alongwith plasticizer may be used as a good film forming materials in the surface coating of leather.